Mechanochemically assisted hydrothermal synthesis of Sn-substituted MFI-type silicates - Kanie, Kiyoshi (Sci Technol Adv Mater, 2018)
Substitution of Al atoms in a zeolite framework by catalytic metal atoms has attracted considerable attention because the catalytic behavior can be tuned by the substituted atoms. In the present study, Sn-substituted MFI-type silicates were synthesized using a hydrothermal reaction of an amorphous Si-O-Sn precursor prepared by mechanochemical grinding of SiO(2) and Sn(OH)(4). The mechanochemical treatment was found to be a key technique for obtaining the amorphous Si-O-Sn precursor, where tetrahedral Sn(4+) species were incorporated into the amorphous matrix. The Sn content in the framework of the MFI-type silicates was successfully controlled by the initial HCl/Si molar ratio of the hydrothermal procedures. Optical reflectance measurements revealed that the Sn(4+) ions were dispersedly incorporated into the silicate framework while preserving the initial tetrahedrally coordinated species. Infrared results imply that the resulting Sn-substituted MFI-type silicate has Brønsted acid character. Precise control of the Brønsted and Lewis acid properties by Sn doping is a promising approach to the development of novel types of zeolite-based catalytic materials.